Guided bone regeneration of peri‐implant defects with particulated and block xenogenic bone substitutes. Issue 5 (13th June 2015) - Benic, Goran I.; Thoma, Daniel S.; Muñoz, Fernando; Sanz Martin, Ignacio; Jung, Ronald E.; Hämmerle, Christoph H. F.
Abstract: Aim: To test whether an equine bone substitute block used for guided bone regeneration (GBR) of peri‐implant defects renders different results from bovine block or particulated bone substitutes regarding the dimensions of the augmented ridge and the amount of new bone. Material and methods: Mandibular premolars and molars were extracted in eight dogs. After 4 months, four semi‐saddle bone defects were created in each mandible and one titanium implant was inserted into every site. Bone augmentation by GBR was attempted using the following randomly assigned modalities: (i) particulated deproteinized bovine bone mineral (DBBM) + a collagen membrane (CM), (ii) block DBBM + CM, (iii) equine bone substitute block + CM, and (iv) empty controls. After 4 months, one central and two lateral sections of each site were prepared. Descriptive histological and histomorphometrical assessments were performed evaluating the augmented area (AA) within the former bone defect, the area of mineralized tissue (MT), non‐mineralized tissue (NMT), and residual bone substitute (BS) within AA, the horizontal thicknesses of the augmented region (HTaugm ) and of the mucosa (HTmucosa ). Results: At the central sections, AA measured 11.2 ± 3.3 mm 2 for the equine block, 9.5 ± 2.6 mm 2 for DBBM block, 7.9 ± 4.8 mm 2 for particulated DBBM, and 2.4 ± 2.1 mm 2 for the empty control. All GBR groups rendered significantly higher values of AA in comparison with control ( P ≤ 0.05). The differences in AA between GBR groups did not reach statistical significance ( P > 0.05). The equine block rendered the highest values in HTaugm, although only the differences between equine block and control as well as equine block and DBBM block were statistically significant ( P ≤ 0.05). With respect to HTmucosa, all GBR groups reached significantly higher values compared to control ( P ≤ 0.05). The equine block revealed the most pronounced signs of graft degradation. Conclusions: Guided bone regeneration lead to higher ridge dimensions and thicker covering mucosa than empty controls. The equine block with CM resulted in the most favorable outcomes regarding the maintenance of ridge contour. There were no significant differences regarding amount of new bone between GBR treatments.